Applying the point target-based calibration approach to ground-based circularly polarized synthetic aperture radar - Izumi Y.; Demirci S.; Bin Baharuddin M.Z.; Sumantyo J.T.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Circularly polarized (CP) synthetic aperture radar (SAR) is a recent state of art SAR that adopts CP-antennas on both a transmitter and a receiver (end-to-end circular polarization). For use of this SAR configuration practically and precisely, in this paper, we propose two types of point target-based polarimetric calibration methods modified by existing calibration for the linearly polarized (LP) radar. Two proposed methods are applied to a ground-based (GB) CP-SAR system to assess the calibration capability on a polarimetric application. The proposed methods yield more accurate entropy-alpha (H-?) distributions than uncalibrated data. The proposed point target-based polarimetric calibration methods can be applied to the wide-frequency bandwidth CP GB-SAR application. 2017 IEEE.